Kaposi's sarcoma-associated herpesvirus gH/gL: glycoprotein export and interaction with cellular receptors. - Hahn, Alexander; Birkmann, Alexander; Wies, Effi; Dorer, Dominik; Mahr, Kerstin; Stürzl, Michael; Titgemeyer, Fritz; Neipel, Frank (Journal of Virology, 2009)
The attachment, entry, and fusion of Kaposi's sarcoma-associated herpesvirus (KSHV) with target cells are mediated by complex machinery containing, among others, viral glycoprotein H (gH) and its alleged chaperone, gL. We observed that KSHV gH, in contrast to its homologues in several other herpesviruses, is transported to the cytoplasm membrane independently from gL, but not vice versa. Mutational analysis revealed that the N terminus of gH is sufficient for gL interaction. However, the entire extracellular part of gH is required for efficient gL secretion. The soluble ectodomain of gH was sufficient to interact with the surfaces of potential target cells in a heparin-dependent manner, and binding was further enhanced by coexpression of gL. Surface plasmon resonance revealed a remarkably high affinity of gH for glycosaminoglycans. Heparan sulfate (HS) proteoglycans of the syndecan family act as cellular receptors for the gH/gL complex. They promoted KSHV infection, and expression of gH/gL on target cells inhibited subsequent KSHV infection. Whereas gH alone was able to bind to HS, we observed that only the gH/gL complex adhered to heparan sulfate-negative cells at lamellipodium-like structures.

The ephrin receptor tyrosine kinase A2 is a cellular receptor for Kaposi's sarcoma-associated herpesvirus - Hahn, Alexander; Kaufmann, Johanna K.; Wies, Effi; Naschberger, Elisabeth; Panteleev-Ivlev, Julia; Schmidt, Katharina; Holzer, Angela; Schmidt, Martin; Chen, Jin; Koenig, Simone; Enßer, Armin; Myoung, Jinjong; et al. (Nature Medicine, 2012)
Kaposi's sarcoma-associated herpesvirus (KSHV) is the causative agent of Kaposi's sarcoma, a highly vascularized tumor originating from lymphatic endothelial cells, and of at least two different B cell malignancies. A dimeric complex formed by the envelope glycoproteins H and L (gH-gL) is required for entry of herpesviruses into host cells. We show that the ephrin receptor tyrosine kinase A2 (EphA2) is a cellular receptor for KSHV gH-gL. EphA2 co-precipitated with both gH-gL and KSHV virions. Infection of human epithelial cells with a GFP-expressing recombinant KSHV strain, as measured by FACS analysis, was increased upon overexpression of EphA2. Antibodies against EphA2 and siRNAs directed against EphA2 inhibited infection of endothelial cells. Pretreatment of KSHV with soluble EphA2 resulted in inhibition of KSHV infection by up to 90%. This marked reduction of KSHV infection was seen with all the different epithelial and endothelial cells used in this study. Similarly, pretreating epithelial or endothelial cells with the soluble EphA2 ligand ephrinA4 impaired KSHV infection. Deletion of the gene encoding EphA2 essentially abolished KSHV infection of mouse endothelial cells. Binding of gH-gL to EphA2 triggered EphA2 phosphorylation and endocytosis, a major pathway of KSHV entry. Quantitative RT-PCR and in situ histochemistry revealed a close correlation between KSHV infection and EphA2 expression both in cultured cells derived from human Kaposi's sarcoma lesions or unaffected human lymphatic endothelium, and in situ in Kaposi's sarcoma specimens, respectively. Taken together, our results identify EphA2, a tyrosine kinase with known functions in neovascularization and oncogenesis, as an entry receptor for KSHV. © 2012 Nature America, Inc. All rights reserved.
Created from Fastlane, Scopus look-up

The Kaposi's sarcoma-associated herpesvirus-encoded vIRF-3 inhibits cellular IRF-5 - Wies, Effi; Hahn, Alexander; Schmidt, Katharina; Viebahn, Cornelia; Rohland, Nadine; Lux, Anja; Schellhorn, Tim; Holzer, Angela; Jung, Jae U.; Neipel, Frank (Journal of Biological Chemistry, 2009)
Kaposi's sarcoma-associated herpesvirus encodes four genes with homology to the family of interferon regulatory factors (IRFs). At least one of these viral IRFs, vIRF-3, is expressed in latently Kaposi's sarcoma-associated herpesvirus-infected primary effusion lymphoma (PEL) cells and is essential for the survival of PEL cells. We now report that vIRF-3 interacts with cellular IRF-5, thereby inhibiting binding of IRF-5 to interferon-responsive promoter elements. Consequently, vIRF-3 blocked IRF-5-mediated promoter activation. A central double helix motif present in vIRF-3 was sufficient to abrogate both DNA binding and transcriptional transactivation by IRF-5. Upon DNA damage or activation of the interferon or Toll-like receptor pathways, cytoplasmic IRF-5 has been reported to be translocated to the nucleus, which results in induction of both p53-independent apoptosis and p21-mediated cell cycle arrest. We report here that IRF-5 is present in the nuclei of PEL cells without interferon stimulation. Silencing of vIRF-3 expression in PEL cells was accompanied by increased sensitivity to interferon- mediated apoptosis and up-regulation of IRF-5 target genes. In addition, vIRF-3 antagonized IRF-5-mediated activation of the p21 promoter. The data presented here indicate that vIRF-3 contributes to immune evasion and sustained proliferation of PEL cells by releasing IRF-5 from transcription complexes. © 2009 by The American Society for Biochemistry and Molecular Biology, Inc.
CRIS-Team Scopus Importer:2022-09-23

The viral interferon-regulatory factor-3 is required for the survival of KSHV-infected primary effusion lymphoma cells. - Wies, Effi; Mori, Yasuko; Hahn, Alexander; Kremmer, Elisabeth; Stürzl, Michael; Fleckenstein, Bernhard; Neipel, Frank (Blood, 2008)
Human herpesvirus-8 (HHV-8), also known as Kaposi sarcoma-associated herpesvirus (KSHV), is etiologically linked to primary effusion lymphoma (PEL). At least 10 KSHV-encoded proteins with potential roles in KSHV-associated neoplasia have been identified. However, with few exceptions, these putative oncogenes were analyzed in heterologous systems only using overexpression of single genes. Thus, the pathogenetic relevance of most of these putative oncogenes remains essentially unclear. We used RNA interference (RNAi) to knock down the expression of several KSHV genes in cultured PEL cells carrying the KSHV genome. The viral interferon-regulatory factor-3 (vIRF-3) was found to be required for proliferation and survival of cultured PEL cells. Knock-down of vIRF-3 expression by various RNAi approaches unequivocally resulted in reduced proliferation and increased activity of caspase-3 and/or caspase-7. Thus, vIRF-3 can be seen as a bona fide oncogene of KSHV-associated lymphoma. Surprisingly, although the related Epstein-Barr virus (EBV) is usually sufficient to immortalize human B lymphocytes, silencing of vIRF-3 reduced the viability of both EBV(-) and EBV(+) PEL cells. This suggests that KSHV is the driving force in the pathogenesis of PEL.